OP V – 2 Prenatal fluoride exposure and neurobehavior among children 1–3 years of age in mexico. (18th March 2018) - Thomas, Deena; Sanchez, Brisa; Peterson, Karen; Basu, Niladri; Angeles Martinez-Mier, E; Mercado-Garcia, Adriana; Hernandez-Avila, Mauricio; Till, Christine; Bashash, Morteza; Hu, Howard; Tellez-Rojo, Martha M
Abstract : Background/aim: Recent studies report an inverse association between fluoride (F) exposure and IQ in children, but few included individual measures of exposure or assessed associations with prenatal exposure using a prospective study design. Methods: This study utilised the Early Life Exposures in Mexico to Environmental Toxicants (ELEMENT) birth cohort and archived pregnancy samples to study prenatal F exposure and its association with subsequent child neurobehavioral outcomes at ages 1, 2 and 3 years. A Generalised Mixed Model (GMM) was used to model the association between mean creatinine-adjusted urinary F (MUFcr), averaged over three trimesters, and Mental Development Index (MDI), a subscale of the Bayley Scales of Infant Development-II (BSID-II) test, among 401 mother-infant pairs. The analysis controlled for maternal age, education, marital status, ELEMENT cohort, child's sex, and child's age. Results: The median MUFcr was 0.835 mg/L (minimum: 0.195, maximum: 3.673). MUFcr was significantly inversely associated with offspring MDI scores, with an increase in MUFcr of 0.5 mg/L (roughly the interquartile range value) corresponding to a decrease in MDI of −1.20 points (95% CI: −2.19, –0.20). Conclusion: Our findings add to our team's recently published report on prenatal fluoride and cognition at ages 4 and 6–12 years by suggesting that higher in utero exposure to F has an adverse impact on offspring cognitive development that can be detected earlier, in the first three years of life.